2014
DOI: 10.1136/bmjopen-2014-005453
|View full text |Cite
|
Sign up to set email alerts
|

Drug efficacy in treating stable angina pectoris: a protocol for network meta-analysis of randomised controlled trials

Abstract: IntroductionThere were 11 pairwise meta-analysis on the efficacy of β-blockers (including atenolol, propranolol, bisoprolol, metoprolol and nadolol), calcium channel blockers (including amlodipine, diltiazem, felodipine, nifedipine and verapamil), and nitrates (including isosorbide dinitrate, isosorbide mononitrate and nitroglycerin) in treating stable angina pectoris. No network meta-analytic study has been published to evaluate the efficacies of these antianginal drugs. Current clinical guidelines (eg, Natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The protocol of systematic reviews and meta-analyses that reported the designs and methodologies before conduct would enhance the study designs and transparency, hence the reliability and reproducibility of evidence [21]. Our study was impartial, valid and reliable in compliant with the pre-speci ed protocol [24,25]. Previous network meta-analyses [19,20] without protocols did not identify the limitations which included PRISMAdiscrepancy, inappropriate model selection based on heterogeneity test, inadequate statistical analysis, and lack of evidence assessment (Supplement 12).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The protocol of systematic reviews and meta-analyses that reported the designs and methodologies before conduct would enhance the study designs and transparency, hence the reliability and reproducibility of evidence [21]. Our study was impartial, valid and reliable in compliant with the pre-speci ed protocol [24,25]. Previous network meta-analyses [19,20] without protocols did not identify the limitations which included PRISMAdiscrepancy, inappropriate model selection based on heterogeneity test, inadequate statistical analysis, and lack of evidence assessment (Supplement 12).…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, their results and conclusions [19,20] were biased and untrustworthy. Our study conducted a rigorous and comprehensive network meta-analysis in accordance with the PRISMA statements [21][22][23] and the pre-speci ed protocol [24,25]. We employed the random-effects model for data synthesis with an assumption of different populations among eligible RCTs [29].…”
Section: Discussionmentioning
confidence: 99%
“…The overall effect sizes will be determined as mean difference for continuous outcomes and ORs for dichotomous outcomes with their 95% credible intervals. Network meta-analysis based on the Bayesian hierarchical model 31 32 of included RCTs will be conducted. The differences in clinical and methodological characteristics among RCTs will be explored by subgroup analysis and sensitivity analysis.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Nadolol Nadolol, a β 3 -adrenoceptor antagonist approved by the FDA, is also used in diverse treatments, such as those for angina pectoris, infantile hemangioma, and hypertension [112][113][114]. Cutaneous vascular lesion, bradycardia, hypotension, and hypoglycemia are the more common adverse events correlated with this drug [115].…”
Section: Wat Browningmentioning
confidence: 99%